Railroad Workers, Civilization and Communism: the Young Men’s Christian Association on the Interwar Polish Frontier - Sylwia Kuźma-Markowska (European Journal of American Studies)
This article seeks to present and analyze one of the aspects of the work of the Young Men’s Christian Association (YMCA or Y) in interwar Poland: the initiatives for railroad workers from eastern frontier towns and cities. Focusing on the efforts that the organization undertook on the territory commonly referred to as the Polish borderlands (Kresy), I show that for the leaders of the Y the work among the railway employees was of utmost political and civilizational importance. There were several reasons why the YMCA became involved in the railroad work on the eastern Polish borderlands. One of them was the looming threat of communism from neighboring Russia, another—the American Y leaders’ mythic perceptions of the U.S. moving frontier, which prompted them to adapt the American discourse on civilization to the Polish political and social situation. Using archival documents and recollections of Americans involved in the Y’s activities on the eastern Polish frontier I demonstrate how the perception of the Polish borderland by the Y’s secretaries was greatly influenced by myths deeply embedded in American culture. Drawing on the contemporary Polish press reports as well as writings of local collaborators of the YMCA, I also describe the reaction of Polish public opinion to the Y’s undertakings on the Polish frontier.